Sistem Advice Planing Online Dengan Framework Codeigniter Berbasis Web Bootstrap (Studi Kasus: Kabupaten Probolinggo) - Moh Ainol Yaqin; Abdullah Al Anis (Politeknik Harapan Bersama, 2018)
The information system in the form of Integrated Advice Planning by using CodeIgniter Framework and based on Framework Bootstrap one of system which gives responsive form. The system is a service as one of solution for e-Government. Advice Planning service is the optimization of public services in the licensing sector and the optimization of agency management. The licensing service is in the form of design consultation and the location of the building in accordance with the Spatial and Regional Plan within a Local Government. Licensing process that must be fulfilled by prospective investors either individually or on behalf of the company and supporting infrastructure around the investment location. The services provided by the Information System have provided Advice Planning application submission online. The system is expected to provide convenience for the community in the region and create a friendly, the comfortable, the transparent and cheap of interaction between the government and the community.